CONTRIBUTIONS REGARDING THE INFLUENCE OF RISKS ON NATURAL PERSONS AND OF THE RISK ASSESSMENT SYSTEM IN THE FIELD OF HEALTH AND SAFETY AT WORK IN THE FRAMEWORK OF DETERGENT PRODUCTION UNITS - Eugenia BULBOACĂ; Oana Roxana CHIVU; Costinel BULBOACĂ; Anda CRÂNGUREANU; Claudia BORDA; Dan NITOI; Marilena GHEORGHE; Pasare VILLI; Ioana - Cătălina ENACHE; Anamaria FEIER (Fiabilitate şi Durabilitate)
Within the units producing detergents, a rigorous analysis of the risk assessment system in the field of OSH of both equipment, personnel and the entire management system is required. The main objective of the ongoing work is to improve the occupational risk assessment system in detergent production units, through theoretical and experimental research in conjunction with the updated legislation according to SR EN ISO 45001/2018. The purpose of the research is to carry out a research and experiments regarding the evaluation of employees and the impact on them among economic units with detergent production. The objectives of the research are: research of an adapted method for the evaluation of the management system in detergent production units; Correlation between specific elements in the field of OSH, measures to improve the evaluation system, aplicability of the management system adapted to the requirements of SR EN ISO 45001/2018, verification of the efficiency of the management system conformed to the new standard, formulation of checklists adapted to the new management standard.